Mediating effect of financial behavior on the relationship between perceived financial wellbeing and its factors among low-income young adults in Malaysia - Sabri, Mohamad Fazli; Wahab, Rozita; Mahdzan, Nurul Shahnaz; Magli, Amirah Shazana; Abd Rahim, Husniyah (Frontiers Research Foundation, 2022)
The main objective of this study is to investigate the associations between financial knowledge, locus of control (LOC) and perceived financial wellbeing (FWB) with financial behaviour as a mediator among young adults from low-income households in Malaysia, controlling for education and income. The sample of this study consisted of 482 young adults from five different zones in Peninsular and East Malaysia, which were selected using a multi-stage sampling technique. Data were collected using a set of questionnaire-based surveys. The data were then analysed using Covariance Based Structural Equation Modelling (SEM). The study found that financial knowledge and external LOC as well as financial behaviour were significantly correlated with the perceived FWB of low-income young adults in Malaysia. The results also revealed that financial behaviour mediates the influence by financial knowledge and internal LOC on perceived FWB controlling for education and income. The findings of this study provide insights into the factors of perceived FWB of low-income young adults in Peninsular and East Malaysia. Policymakers, government and non-government organisations may utilise this study to develop new policies, financial programmes or campaigns to enhance the FWB of low-income young adults in Malaysia.